1989
DOI: 10.1200/jco.1989.7.12.1875
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of metastatic renal cell carcinoma with a biologically active dose of recombinant interferon-gamma.

Abstract: We tested the clinical efficacy of a biologically active dose (BAD) of interferon (IFN)-gamma for treatment of progressive renal cell carcinoma (RCC). Twenty-two RCC patients with disease progression subsequent to nephrectomy were entered on a phase II clinical trial. During an initial dose-finding phase, biochemical responses to repeated once-weekly subcutaneous injections of 10, 100, or 500 micrograms of recombinant IFN-gamma were tested in 16 patients. Results indicated that 100 micrograms IFN-gamma applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 29 publications
3
43
0
3
Order By: Relevance
“…Interferon-alpha (IFN-alpha) and interleukin-2 (IL-2) have proved most effective agents with an overall response rate of 14 and 18%, respectively [2]. Similar results were obtained with a low-dose interferon-gamma (IFN-gamma) monotherapy [3], We present a 58-year-old female with metastatic RCC treated with an alternating regime of IFN-gamma and combined IFNalpha/IL-2. Immune therapy with subcutanous IFN-alpha and recombinant IL-2 was started in September 1989.…”
Section: Schlußfolgerungsupporting
confidence: 66%
See 1 more Smart Citation
“…Interferon-alpha (IFN-alpha) and interleukin-2 (IL-2) have proved most effective agents with an overall response rate of 14 and 18%, respectively [2]. Similar results were obtained with a low-dose interferon-gamma (IFN-gamma) monotherapy [3], We present a 58-year-old female with metastatic RCC treated with an alternating regime of IFN-gamma and combined IFNalpha/IL-2. Immune therapy with subcutanous IFN-alpha and recombinant IL-2 was started in September 1989.…”
Section: Schlußfolgerungsupporting
confidence: 66%
“…Abdominal CT: diameter of liver mass 5.5 x 6 cm, small increase in comparison to January. Therefore, we started a therapy with low-dose recombinant IFN-gamma (Polyferon®, Rentschler, Lauphcim, Germany) [3]. It was injected subcu taneously once a week at a dose of 150 pg.…”
Section: Schlußfolgerungmentioning
confidence: 99%
“…Thus the IFN-␥-induced cell injury might be related to its effects on K ϩ channel activity. It is also of note that IFN-␥ is sometimes used for the treatment of renal cell carcinoma (2,18). Considering that it might cause renal cell injury, special attention should be paid to its therapeutic use.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical benefit is not long lasting and is often accompanied by serious toxicity. 6,[46][47][48] One study reported good clinical responses following systemic IFN␥ treatment 49 but similar results have not been seen in other patients. 6,50,51 Because of the toxicities associated with systemic interferon application this form of treatment is not suitable for patients with low performance status or as an adjuvant therapy for patients with minimal residual disease.…”
Section: Discussionmentioning
confidence: 94%